1978
DOI: 10.1113/expphysiol.1978.sp002430
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Analogues of Arginine‐vasopressin (Ornithine‐vasopressin and Desamino‐d‐arginine‐vasopressin) on Kidney Function in Sheep

Abstract: The effects of intravenous infusion of ornithine-vasopressin (OVP) and desamino-D-argininevasopressin (dDAVP) were studied in normal and hydrated Merino sheep. In normal sheep, OVP resulted in a diuresis, increased urinary sodium and potassium excretion, and a fall in the plasma potassium concentration. Renal plasma flow remained constant but glomerular filtration rate and filtration fraction rose markedly. dDAVP in normal sheep was antidiuretic, but its only significant effect was a small decrease in plasma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…infusion (1.13 pmol•kg −1 •min −1 , ~30 mcL/min), beginning 1 hour after pneumonia induction and maintained for the remainder of the 24-h study period in addition to the titrated infusion of selepressin that was started and continued as described above. This infusion rate of dDAVP was shown to be antidiuretic in hydrated sheep (39) and was kept constant to magnify any potential effect of V 2 R activation. The infusion was started 1 hour after pneumonia induction to allow for plasma dDAVP concentration to closely approach steady-state by the time MAP levels would decrease sufficiently for selepressin infusion to be started—dDAVP infusion requires 2 hours to reach steady-state plasma concentration in sheep compared to 30 minutes for AVP (40, 41).…”
Section: Methodsmentioning
confidence: 99%
“…infusion (1.13 pmol•kg −1 •min −1 , ~30 mcL/min), beginning 1 hour after pneumonia induction and maintained for the remainder of the 24-h study period in addition to the titrated infusion of selepressin that was started and continued as described above. This infusion rate of dDAVP was shown to be antidiuretic in hydrated sheep (39) and was kept constant to magnify any potential effect of V 2 R activation. The infusion was started 1 hour after pneumonia induction to allow for plasma dDAVP concentration to closely approach steady-state by the time MAP levels would decrease sufficiently for selepressin infusion to be started—dDAVP infusion requires 2 hours to reach steady-state plasma concentration in sheep compared to 30 minutes for AVP (40, 41).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of AVP infusion at 115 pmol (5 mU).min-l were in every way similar to those produced by the infusion of the pressor analogue, ornithine-vasopressin (OVP), at a dose rate of 13 3pmol (5mU).min-1 [Yesberg, Henderson and Budtz-Olsen, 1978], except that the marked increase in UNaV and fall in Posmol, which were statistically insignificant during OVP infusion, were highly significant during AVP infusion. Many of the effects of OVP on renal function in either hydrated or non-hydrated sheep were shown to be dependent on the pressor activity of the hormone molecule since they did not occur with the nonpressor analogue, desamino-D-arginine-vasopressin.…”
Section: Resultsmentioning
confidence: 72%
“…AVP can also raise glomerular filtration rate (GFR) in these sheep [Yesberg, Henderson and Budtz-Olsen, 1973], and experiments with analogues of AVP suggest that the diuretic and electrolyte-excreting effects are dependent on the vasopressor activity of the hormone molecule and that they occur as a result of an increase in filtration fraction from an unaltered renal plasma flow (RPF) [Yesberg, Henderson and Budtz-Olsen, 1978]. The increase in endogenous AVP in response to dehydration is nevertheless associated with a decrease in water and electrolyte output [Yesberg, Henderson and Budtz-Olsen, 1970] and a fall in GFR and RPF [McDonald and Macfarlane, 1958].…”
mentioning
confidence: 99%
“…Scott and Morton [1976] showed that the same dose rate of hypertonic saline raised plasma AVP levels three or four times, and these were similar to PAVP levels resulting from an infusion of I1I5 pmol.min-'. We have shown that AVP at a dose rate of 46pmol.min-t [Yesberg et al, 1973] and 11 5 pmol.min-' [Yesberg, N.E., unpublished] and that ornithine-vasopressin at a dose rate of 13'3 pmol.min-' [Yesberg et al 1978] can increase GFR significantly, though RPF remains unchanged, resulting in a rise in FF. It is possible therefore that the increase in GFR in the present experiments was at least partly due to the increase in AVP levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that AVP can increase glomerular filtration rate (GFR) in such sheep [Yesberg, Henderson and Budtz-Olsen, 1973] and have suggested that this could at least partly account for the increased electrolyte excretion as well as the diuresis [Yesberg, 1974]. These effects on water and electrolyte excretion and GFR have also been observed with the pressor analogues of AVP, lysine-vasopressin and ornithine-vasopressin [Yesberg, 1974] but not with the non-pressor analogue, desamino-D-arginine-vasopressin [Yesberg, Henderson and Budtz-Olsen, 1978]. It might be argued that these observations are responses to pharmacological amounts of the hormone, but Scott and Morton [1976] showed that intravenous hypertonic saline loading caused the release of endogenous AVP which was associated with, and probably the cause of, an increased water and salt excretion, and that the plasma AVP levels achieved were similar to those produced by an exogenous AVP infusion rate of 11-5 pmol.…”
mentioning
confidence: 99%